Sistema crediticio de Produbanco s.a. y su incidencia en el desarrollo de las pymes del Cantón Quevedo, Año 2015. - Fuentes Valenzuela, Gabriela Patricia (2016)
This research project deepens the study on the Administrative Management of the Bank of Production S.A. PRODUBANCO, and its impact on the development of SMEs in Quevedo. The analysis of the problem allowed to know the different aspects that revolve around the complex business world of SMEs, their economic development, the possibilities of accessing the financial services and credits provided by PRODUBANCO. It also made it possible to write the objectives of the research (general and specific); developing the conceptual and theoretical framework; Field research; a work that is justified by its relevance, utility (beneficiaries) and its feasibility, which shows the expected results. The theoretical framework develops a set of topics regarding the administrative management of the Bank of Production S.A. PRODUBANCO, SMEs, and its economic activity, among others. As for the methodology, the research modality used was the qualitative one, because it performs an interpretation of theoretical aspects around the object of study; and qualitative, by the statistical representation of the results of field research. The methods used were: the deductive, inductive and scientific; among the techniques: direct observation, surveys and interviews. To calculate the sample of the total population of SMEs in Quevedo, a statistical formula was used, the population to which the surveys and interviews were applied. Resultsthatwereanalyzed and interpreted.